Development of an on-job mentorship programme to improve nursing experience for enhanced patient experience of compassionate care - Alma Arshad Hookmani; Naureen Lalani; Noureen Sultan; Aly Zubairi; Ayesha Hussain; Babar S. Hasan; Muneera A. Rasheed (BMC, 2021)
Abstract Background Evidence suggests improvement in nursing staff satisfaction, competence, and retention after implementation of evidence-based mentorship programmes. When guided by a framework of compassion, mentoring as a caring action can not only build healthy, transformative relationships but a similar behavior is reciprocated to patients which subsequently can drive patient experience of care. However, examples of on-job mentorship programs for nurses in low- and middle-income countries (LMIC) are limited. Objective The objective of the study was to develop an on-job nursing mentorship programme using a compassionate framework aimed at improving nurses' experience and thus enhancing patient experience in a tertiary care hospital in Pakistan. Methods Designed as an intervention development study, it was completed between January 2018-December 2019. The programme was developed by a team composed of service and nursing leadership, director patient experience of care and a compassion specialist using a theory of change model. The package followed a series of steps, a) identification of a framework, b) creation of working group c) needs assessment and d) multiple meetings to frame the model followed by implementing the preconditions for roll-out of the programme with the frontline staff. Results The eventual outcome was improving the patient's experience of compassion while the intermediate outcome was to have nurses demonstrate compassionate care. The pre-conditions were identified as: recruitment of staff with appropriate skills for pediatric care, provision of compassionate experience to the frontline nurses by addressing their specific pain points, development of competent head nurses as supervisors and creation of a compassionate culture. To ensure the pre-conditions, various interventions were planned with some implemented through the course of the study while others are in the process of being rolled out. These involved, inclusion of pediatric compassion specific module during orientation of new hires, creation of space to talk about compassionate skills with staff, provision of trainings and mentorship to create competent head nurses, and creating a culture that promoted and recognized compassionate care values. Conclusion The approach helped to delineate feasible pathways for an on-job compassionate mentorship programme enhancing routine supervisors' role as facilitators of compassionate care.